RANCANG BANGUN AUGMENTED REALITY APLIKASI PENGENALAN KAIN ULOS TRADISIONAL SUMATERA UTARA MENGGUNAKAN METODE MARKERLESS - simanullang, enilda; Simanjuntak, Pastima Siman (LPPM Universitas Putera Batam, 2021)
Wearing the Toba Batak Traditional Ulos is one of the values ​​that is strongly attached to the Toba Batak Tribe custom. Where the ulos has various types and different functions. The problem faced by school teachers in presenting and introducing these types of ulos is the lack of teaching aids. In the world of education, especially in elementary schools, it will feel boring if the delivery of the material is still conventional, still focusing on only using books. To keep up with the times, don’t forget that scienceand technology will also experience developments. With this development, an application was made which is a learning media using technology to help the learning and teaching process. To make it easier to recognize Ulos, it was made based on Android and utilized augmented reality technology in 3D. In designing this application there are also data collection methods such as direct interviews to schools because this will greatly assist teachers in learning to introduce Ulos Batak Toba. The researcher also provides 2D objects made in the bookmark book as a reference to display Ulos with 12 types of Ulos in 3D and along with the functions of the types of Ulos